Dynamics on Wild Character Varieties - Paul, E.; Ramis, J.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
In the present paper, we will first present briefly a general research program about the study of the ''natural dynamics'' on character varieties and wild character varieties. Afterwards, we will illustrate this program in the context of the Painlevé differential equations PVI and PV.